Ivabradine Ameliorates Cardiac Diastolic Dysfunction in Diabetic Mice Independent of Heart Rate Reduction - Xie, Hao; Shen, Xing-Yi; Zhao, Na; Ye, Peng; Ge, Zhen; Hu, Zuo-Ying (Frontiers in Pharmacology, 2021)
Cardiac fibroblast (CF) proliferation and activation play important roles in cardiac fibrosis and diastolic dysfunction (DD), which are involved in fibrosis-associated cardiovascular diseases. A previous study showed that ivabradine, a specific heart rate (HR)-lowering agent, significantly ameliorated DD in diabetic db/db mice by reducing HR. Herein, we attempted to determine whether ivabradine has antifibrotic and cardioprotective effects in diabetic mice by directly suppressing CF proliferation and activation, independent of a reduction in HR. We found that knockdown of c-Jun N-terminal kinase (JNK) or p38 mitogen-activated protein kinase (MAPK), or treatment with ivabradine, reduced JNK and p38 MAPK phosphorylation and the protein expression of proliferating cell nuclear antigen, collagen I, collagen III, tissue inhibitor of matrix metalloproteinase 2, and α-smooth muscle actin, accompanied with upregulation of matrix metalloproteinase 2 both in high glucose-treated neonatal rat CFs and left ventricular CFs isolated from db/db mice. However, zatebradine (a HR‐lowering agent) did not have these effects in vitro or in vivo. In addition, cardiac fibrosis and DD were ameliorated in db/db mice that were intravenously administered lentiviruses carrying short hairpin RNAs targeting JNK and p38 MAPK or administered ivabradine. Taken together, these findings demonstrate that the ivabradine-induced amelioration of cardiac fibrosis, and DD in db/db mice may be at least in part attributable to the suppression of CF proliferation and activation, through the inhibition of JNK and p38 MAPK.